Web Server Security Analyzation Tool - Kopecký, Samuel (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2021)
Nowadays it is common practice to have a securely hosted web server. To have a secureweb server it is required to ensure that CIA (Confidentiality, Integrity, Availability) triad is in place.CIA triad is fulfilled by using different mechanisms like symmetric cryptography and public keyinfrastructure. These mechanisms on the other side use a set of algorithms and parameters. Thispaper focuses on the automation of analyzing the security of these algorithms, parameters and alsovulnerability testing.
Keywords: SSL; TLS; Web Server; Automation; Security; Analyze